Partisipasi aktif dalam ibadah online sebagai tanda persekutuan - Pakpahan, Binsar Jonathan (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2022)
This article aims to explain the differences between the online community and fellowship (church) through the dimensions of active participation in online worship. A fellowship is a community of baptized who confessed their faith and are actively involved in their calling. In a local church, members are united by common culture, language, and history. It is feared that online worship carried out during the Covid-19 pandemic will reduce the meaning of fellowship. Through descriptive qualitative method plus observation, with the theory from Alan Rathe and F. Gerrit Immink regarding active participation, this study found three indicators that could help churches prepare their worship to invite active participation as a sign of fellowship. The three indicators are “in” which refers to the common ground, namely initiation in the Triune God;